Is Radiologic Evaluation Necessary to Find out Foreign Bodies in Nasal Cavity?. Issue 1 (January 2016) - Oh, Hoon; Min, Hyun Jin; Yang, Hoon Shik; Kim, Kyung Soo
Abstract : Abstract: Although there were previous studies on the clinical aspects such as etiology, treatment modalities, studies regarding the necessity of radiologic evaluation for nasal foreign body were limited. The aim of this study is to evaluate the necessity and indication of radiologic evaluation for nasal foreign bodies. There are consecutive patients aged less than 10 years who presented with suspected foreign bodies in nasal cavity. We reviewed the patient's age and sex, including the methods of evaluation, management tools, and types of foreign bodies. There were 35 cases (11.4%) on whom radiographs were performed in the 24 uncooperative patients and 11 cooperative patients who were not identified with any foreign bodies via nasal endoscopy. Among them, only 4 cases had positive reports of foreign body and the others were normal radiologic findings. We suggest that the radiologic evaluation is always not necessary to find the location of nasal foreign bodies. It, however, should be performed in cases of negative findings of physical examination with anterior rhinoscopy or sinus endoscopy and unwitnessed foreign bodies to rule out metallic contents, especially button type battery.